1980
DOI: 10.1093/geronj/35.6.836
|View full text |Cite
|
Sign up to set email alerts
|

Neuron Loss in the Aging Visual Cortex of Man

Abstract: Measured by a cell dispersion technique, the neuron population densities of the macular projection areas of 23 individuals aged 20 to 87 years fell from about 46 million neurons per gram of tissue of age 20 to about 24 million neurons per gram at age 80. A corresponding increase in glial cells was found in the gray and subjacent white matter. Since the older brains showed a significant decrease in mass, the decrease in neuron population density could only reflect an absolute loss of neurons proportional to or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
82
2
1

Year Published

1984
1984
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(89 citation statements)
references
References 0 publications
4
82
2
1
Order By: Relevance
“…This result received a great deal of publicity, and stimulated a number of other studies carried out in the 1970s and 1980s in which similar decreases in neuronal density with age were reported (e.g. Colon, 1972;Shefer, 1973;Devaney and Johnson, 1980;Henderson et al, 1980;Anderson et al, 1983). During that period, the only investigator who seemed to disagree with the conclusion that there is a significant loss of neurons with age was Cragg (1975), who found no differences in neuronal density in the frontal and temporal cortices with age.…”
supporting
confidence: 53%
“…This result received a great deal of publicity, and stimulated a number of other studies carried out in the 1970s and 1980s in which similar decreases in neuronal density with age were reported (e.g. Colon, 1972;Shefer, 1973;Devaney and Johnson, 1980;Henderson et al, 1980;Anderson et al, 1983). During that period, the only investigator who seemed to disagree with the conclusion that there is a significant loss of neurons with age was Cragg (1975), who found no differences in neuronal density in the frontal and temporal cortices with age.…”
supporting
confidence: 53%
“…The decline is consistent with the linear increase in logarithm threshold of vision which was described by Hinchcliff (1962) in his analysis of ageing changes in the central nervous system, though it is at variance with the time course derived by Weale (1975Weale ( , 1982 from visual acuity data. The basis for the continuous decline from the third decade onwards may possibly be in the fall in the numbers of retinal and cortical neurones occurring over this period (Hinchcliff, 1962;Devaney & Johnson, 1980;Gartner & Henkind, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Weale (1963), who originally ascribed the major portion of age-related VF DLS loss to preretinal factors, later suggested that the cell loss within the central optic pathway is the major factor in the age-related decline in sensitivity (Weale 1983). Many histological studies have shown that age-related reductions in photoreceptor density (Marshall et al 1979;Gartner & Henkind 1981;Dorey et al 1989;Gao & Hollyfield 1992;Curcio et al 1993), photopigment density (van Norren & van Meel 1985;Kilbride et al 1986), the number and morphology of optic nerve axons (Dolman et al 1980;Balazsi et al 1984;Sommer et al 1984;Repka & Quigley 1989) and the population density of neurons in the visual cortex (Devaney & Johnson 1980) do exist. Several studies have assumed a linear decrease in threshold values with age (Drance et al 1967a(Drance et al , 1967bEgge 1984;Flammer 1985;Brenton & Phelps 1986;Haas et al 1986;Jaffe et al 1986;Heijl et al 1987;Zulauf et al 1994a;Koller et al 2001;Okuyama et al 2001;Heijl 2005), whereas many authors have described a non-linear mathematical model or found a change point, demonstrating an increasing loss of sensitivity at a specific age (Derefeldt et al 1979;Iwase et al 1988;Vivell et al 1992;Lachenmayr et al 1994Lachenmayr et al , 2001Adams et al 1999;Lorch et al 2001;…”
Section: Ageingmentioning
confidence: 99%
“…Dolman et al (1980) reported on a loss of axons with increasing age, which was particularly marked from 60 years of age. Devaney & Johnson (1980) ascertained that the population density of neurons in the visual cortex falls mainly between the third and sixth decades.…”
Section: Ageingmentioning
confidence: 99%